When is a doll's house not a doll's house? - Vale, Brenda; Vale, Robert (Architectural History Aotearoa, 2018)
Claimed as the smallest house in Australia, the Doll's House was a tiny two-roomed dwelling from the 1870s that became the poorest house in the then poorest suburb of Melbourne (Collingwood). It has since earned heritage status being cited by the National Trust in 1985 and later registered as a historic building. The miniature proportions of this tiny worker's cottage are the reason behind its nickname. This fascination with the miniature produced houses at much smaller scales as the residences of dolls rather than people. This paper examines the difference between the dolls' houses of the "old country" of the period and those that resulted from the need to make do with the resources at hand in the new colonies. Between the 1870s and the end of the nineteenth century the former were moving from bespoke houses for the very wealthy to mass-produced toys for the middle classes. German firms like Gottschalk were exporting their dolls' houses and mass-produced furniture for these to the UK and elsewhere in imitation of the exteriors and interiors of the period. In Australia dolls' houses of this period were made from waste materials such as packing cases. Furnishings could also be handmade, perhaps to the suggestions of Mrs Beeton, who encouraged children to make their own dolls' house furniture. The paper speculates as to whether this might also have been the situation in New Zealand. Unfortunately, no homemade dolls' house dating back to 1870 has yet been located here.